ANALISIS KELAYAKAN PENAMBAHAN MESIN KEBI DI PABRIK BERAS - Ihfadlotul Khoiriyah; Setijanen Djoko Haridjanto (LPPM Universitas Bina Bangsa, 2023)
UD Sumber Tani is a rice production business located in the Gresik region. Along with seeing the increasing demand for rice products and increasing profit generation. UD Sumber Tani seeks to increase production capacity by adding machine facilities, namely kebi (polisher) machines. In this effort, it requires a further effort in analyzing the addition of the kebi machine. Due to the expensive selling value of the machine. The analysis carried out is to analyze from various feasibility aspects including market, technical and financial. In the financial aspect, it includes NPV, IRR, and Payback Period. The results of the analysis obtained include market and technical aspects are said to be feasible by weighing product demand, machine specifications, layout and so on. Meanwhile, in the financial aspect, it was found that the NPV of IDR 1,696,324,627 â‰¥ 0 was said to be feasible, IRR was 58% â‰¥ MARR and the return that occurred in the addition of this machine was one year faster than the economic value of the machine. The addition of machines at UD Sumber Tani by conducting a series of analyses is said to be feasible